Opportunistic infections among schoolchildren who were on antiretroviral therapy in Ethiopia: a systematic review and meta-analysis - Birhanu, Molla Yigzaw; Telayneh, Animut Takele; Kassie, Abere; Tegegne, Eniyew; Jemberie, Selamawit Shita (Frontiers in Pediatrics, 2024)
Introduction The most common and severe cause of morbidity and mortality among HIV- positive children is opportunistic infections (OIs). All HIV-infected children are at risk of developing a variety of OIs. Healthcare workers, programmers, and other stakeholders are in doubt about using the onset and predictors of OIs among schoolchildren on antiretroviral therapy (ART) due to the presence of conflicting results found in the primary studies. Hence, this study was conducted to provide a single figure of onset and specific predictors of OIs by overcoming the existing heterogeneity in Ethiopia. Methods The included studies were searched from different national and international databases systematically. The included studies were cohort in design and published in English between 2015 and 2022. The data were extracted using a validated Microsoft Excel tool after the quality of the included studies was assured. The extracted data were exported to Stata Version 17.0 for further management and analysis. The presence of heterogeneity across studies was checked using the Chi-square test and quantified using the I2 test. Various methods, including forest plots, publication bias assessment, sensitivity tests, subgroup analysis, and meta-regression, were employed to determine the source of heterogeneity, but none were successful. The overall onset of OIs was estimated by pooling the incidence of primary studies using a random-effects meta-analysis model. The predictors were identified using meta-regression and the presence of significant association was declared using a p-value of 0.05 with 95% CI. The strength of association was reported using an adjusted hazard ratio with 95% CI. Results Eleven studies were included in this systematic review and meta-analysis. The onset of OIs among schoolchildren on ART in Ethiopia was 5.58 (95% CI: 4.50, 6.67) per 100 children-years of OI-free observations. Those children who had no parents had a 1.41 (95% CI: 1.10, 1.80) times higher chance of getting OIs when compared with those children having one or both parents. Children who had poor ART adherence had a 2.96 (95% CI: 1.66, 5.29) times higher chance of experiencing OIs than children who had good ART adherence. Finally, the chance of experiencing OIs among rural children was 2.15 (95% CI: 1.63, 2.83) times higher than their counterparts in Ethiopia. Conclusions Three in every 33 schoolchildren on ART developed OIs in Ethiopia. Predictors of OIs included schoolchildren without parents, those with poor adherence to ART, and rural residents. This suggests that social support, medication adherence, and access to healthcare services may play important roles in preventing and controlling OIs among schoolchildren living with HIV in rural areas.